Storm rising : a thriller - Hauty, Chris (Hauty, Chris. Hayley Chill thriller, 2022)
"A mystery from covert agent Hayley Chill's past leads her into the depths of a white supremacy conspiracy that threatens to ignite a second Civil War"--